Climate Change Education in a Secondary School, the I‐CHANGE Project Approach - Devecchi, Monica; Dagnino, Elisa; Milelli, Massimo; Soini, Katriina; Parodi, Antonio (John Wiley & Sons, 2024)
Raising the awareness and interest of young generations for climate change phenomena and its impacts is a topic of great importance from a social and cultural standpoint. Along these lines, education plays a crucial role to meet the goals of the EU's Green Deal both through direct interplay with students and information spillover towards families and in general stakeholders at large. Inspired by these ideas, the H2020 I-CHANGE project (Individual Change of HAbits Needed for Green European transition, 2021–2025, https://ichange-project.eu/) aims at engaging and promoting the active participation of citizens for addressing climate change, sustainable development, and environmental protection. By taking into consideration the ongoing fast socio-cultural change, the vertical growth of digital media, and, therefore, the new ways children and young people learn, this paper presents a possible path towards the practical implementation of key EU's Green Deal concepts in a secondary school, building on top of Episode of Situated Learning (ESL) methodology.
Keywords: citizen science; climate change; H2020 I-CHANGE